Aerobic Exercise Attenuates Acute Lung Injury Through NET Inhibition - Shi, Yue; Liu, Tingting; Nieman, David C.; Cui, Yanqiu; Li, Fei; Yang, Luyu; Shi, Hui; Chen, Peijie (Frontiers in Immunology, 2020)
Aerobic exercise improves lung inflammation in acute lung injury (ALI) but its mechanism remains unknown. Neutrophil extracellular traps (NETs) play an important role in LPS-induced ALI, and a positive correlation exists between NETs formation and proinflammatory macrophage polarization. This study investigated whether aerobic exercise reduces the pro-inflammatory polarization of alveolar macrophages (AMs) by inhibiting the excessive release of NETs, then alleviating the inflammatory response of ALI. Methods: C57BL/6 male mice were randomly divided into four groups: sedentary group (CON), sedentary and extra-pulmonary LPS injection group (LPS), 5-weeks aerobic training intervention and LPS injection group (EXE+LPS), DNase I plus LPS injection group (DNase+LPS). 24h after drug injection, bronchoalveolar lavage fluid (BALF), AM, and lung tissues were obtained to detect inflammatory responses, NETs formation, macrophage polarization, and proteins activation. In the vitro study, murine AMs cell line designated MH-S, were stimulated with LPS, purified NETs and NETs plus DNase I. Results: EXE+LPS and DNase+LPS mice exhibited reduced neutrophil infiltration, decreased NETs release, and lower pro-inflammatory polarization of AM compared with LPS mice. Subsequently, western blot showed inhibition of the phosphorylation of MAPK and NF-κB proteins of AMs in EXE+LPS and DNase+LPS mice compared with LPS mice. Lastly, stimulation of MH-S cells by NETs revealed a trend for pro-inflammatory cell polarization, with NF-κB protein activation at 8 hours and ERK1/2 activation at 1 hour, 2 hours and 8 hours. Conclusions: Aerobic exercise alleviated ALI through NETs induced AMs pro-inflammatory polarization involving ERK1/2 and NF-κB signaling.